Review: Medication Error in Prescribing and Dispensing Phases on Outpatient: Review: Medication error dalam fase peresepan dan dispensing pada Pasien Rawat Jalan - Anwar, Ismail; Sinala, Santi; Nurisyah, Nurisyah; Adhayanti, Ida; Dewi, Sisilia Teresia Rosmala (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2022)
Background: A medication error is defined as "any preventable event that may cause or lead to inappropriate medication use or patient harm while the medication is in the control of the healthcare professional, patient, or consumer." A medication error might occur at any point during the medication-use process, such as when prescribing the medicines, during dispensing, and when the drug is taken by the patient. Objectives: This review focusing on the types of medication errors (MEs) which commonly occurs during prescribing and dispensing phase on the outpatient in Indonesia. Material and Methods: Articles related to MEs during prescribing and dispensing phase were collected from DOAJ (Directory of Open Access Journals) and google scholar. The articles were reviewed and analyze to draw conclusions about the common type of MEs mostly occured on the outpatients. There were 10 articles (2003-2020) that have been reviewed, covering the types of MEs, MEs incidents and how to reduce the number of MEs incident. Results: Based on the reviewed articles, MEs commonly occured in the prescribing phase were incomplete data of patient's on the prescription include address, born date, weight and gender; unclear information on the prescription including, dosage, route of adminstration, illegible writing; uncomplete data on the doctor's information such as the practise license number wasn't listed, and there were no information on medicine interactions. MEs occured during dispensing phase were uncomplete data on the information about how to use, time of using, indication, the amount of the drug given, the side effects, the storage instruction, the strength or the doses of medicine, error in writing etiquette, error in compounding as well as there was no information related what to do if the patient forgot to take the medicines.